Analisis Proses Berpikir Siswa Ditinjau dari Adversity Quotient pada Materi Lingkaran - Hidayah, Suci Wahyuni Nur; Rahmah, Nur; Lestari, Alia (Circle: Jurnal Pendidikan Matematika, 2024)
This research aims to understand students' thinking processes in terms of the adversity quotient for the climber, camper and quitter types. This type of research is qualitative research that focuses on description. This research was carried out by giving questionnaires, test sheets and interview sheets to class VIII students at MTsN Palopo. The results of this research show that there are several very significant differences in the thinking process in terms of the adversity quotient, namely between climber, camper and quitter type students. 1) Climber type students have a high enthusiasm for learning, tend to experience conceptual thinking processes in solving problems. 2) Camper type students have moderate enthusiasm for learning, tend to experience semi-conceptual thinking processes in solving problems. 3) Quitter type students have low enthusiasm for learning, tend to experience computational thinking processes in solving problems.